Views of Mathematics Teacher Candidates on the Use of GeoGebra in Probability Teaching - Kuzu, Cigdem Inci (Asian Journal of Contemporary Education, 2021)
In this study, it was aimed to reveal the opinions of mathematics teacher candidates about the use of the GeoGebra program, which is dynamic geometry software, in the teaching of probability, which is among the concepts that we generally use in the decision-making process in uncertain situations that we encounter in the teaching process by teachers and students. Within the scope of this purpose, a total of 65 elementary mathematics teacher candidates, who have taken statistics and probability courses at a state university, were given GeoGebra training for 4 weeks and made applications. After the training, a semi-structured opinion questionnaire consisting of 5 questions developed by the researchers was applied to the pre-service teachers. Besides, each participant was interviewed. The study is a case study, and the content analysis method was used in the analysis of the data. It has been determined that it is difficult to write equations in the subject of probability processed through GeoGebra and although it provides result-oriented solutions, it provides good and permanent learning in the context of reaching more sample solutions in a short time, it provides a pleasant, non-monotonous and interesting lesson opportunity by concretizing the subject. Also, it was concluded that dynamic elements provide permanence, but there may be difficulties in applications due to the lack of knowledge of computer use by teachers and students.